Global financial crisis, ownership and bank profit efficiency in the Bangladeshs state owned and private commercial banks - Kamarudin, Fakarudin; Sufian, Fadzlan; Md. Nassir, Annuar (Universidad Nacional Autónoma de México, 2016)
This paper studies the impact of global financial crisis focusing on State Owned Commercial Banks (SCBs) and Private Commercial Banks (PCBs) ownership and others bank specific and macroeconomics factors influencing profit efficiency level of the Bangladesh banking sector. The Slack-Based Data Envelopment Analysis (SBM-DEA) method employed to compute the profit efficiency of 31 commercial banks operating in the Bangladesh over the years 2004–2011. Furthermore, the multivariate panel regression analysis framework based on the Ordinary Least Square (OLS) and Generalized Least Square (GLS) methods comprising the Fixed Effect (FE) and Random Effect (RE) models adopted to examine the determinants of banks profit efficiency. Results indicate the levels of profit efficiency on SCBs and PCBs are increasing by 3.7% and 5.8% during financial crisis years. However, over the period of post financial crisis years exhibited, profit efficiency levels on SCBs and PCBs are decreasing by 38.7% and 9.9%. Although profit efficiency levels on both ownership of banks show declining over the post financial crisis years, the PCBs still higher than SCBs (67.8% > 60.1%) but insignificantly different. Furthermore, the findings reveals that the relationship of size of bank, liquidity, economic growth and market concentration are significantly negative with profit efficiency of SCBs but positive to PCBs. Meanwhile, the factors of capitalization, credit risk and inflation are significant with the positive and negative sign only to the profit efficiency of the SCBs over the period of post global financial crisis.